AUDIT KEAMANAN SISTEM INFORMASI AKADEMIK DENGAN KERANGKA KERJA ISO 27001 DI PROGRAM STUDI SISTEM INFORMASI UNIKOM - Winanti, Marliana Budhiningtias; Dzulhan, Ismail (Universitas Komputer Indonesia, 2018)
Academic Information Systems Prodi UNIKOM Information System is the primary system used in the Information Systems Prodi process data and information about lectures and students. But in this system still found a lack of control of physical and logical security. To find out how your system security in organizations, information systems need security audit to determine whether security information is in accordance with the security procedures of management. Standardization used here is ISO 27001, this standards have been an international standards organization that is structured on the management of information security systems. Implementation of academic information system security audit is done by using the Audit Checklist ISO 27001: 2005. Audit results found security controls are still less well as the roles and responsibilities of employee safety, physical protection from disasters and power failures, data validation, and data backup are less regular. So the academic information system security controls is still need to be repairs in accordance with the recommendation.